К ВОПРОСАМ ИСТОРИИ И ЭТНОГРАФИЧЕСКИХ ОСОБЕННОСТЕЙ АЗЕРБАЙДЖАНСКОГО КОВРА. - Алиев, С. (Journal of Oriental Studies, 2016)
Автор мақалада Әзірбайжан кілемінің этнография- лық ерекшеліктері мен тарихы туралы мәселелеріне тоқталады. The article is devoted to development way of the Azerbaijan carpet weaving and ethnographic characteristics of the Azerbaijan carpet. The Article also analyses the specifics of the Azerbaijan carpets on regions under the sources and ethnographic materials, provides information about individual carpet schools and the role and place of carpets in the home and the culture of the people are provided.